Incidence and factors associated with bronchopulmonary dysplasia in discharges from Neonatal Intensive Care Units in Northern Minas Gerais - Micheline Soares Diniz Menezes; Victor Figueiredo Dias; Diego Dias de Araújo; Jair Almeida Carneiro; Lucineia de Pinho; Antônio Prates Caldeira (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to evaluate the incidence and factors associated with bronchopulmonary dysplasia (BPD) in premature infantsdischarged from Neonatal Intensive Care Units (NICU). Methods: retrospective cohort study with premature infants discharged from the NICU. The sampling process was random, considering premature infants being followed up at a high-risk outpatient clinic registered in a NICU from 2014 to 2018. The collection was carried out from medical records and interviews with mothers or guardians, with information regarding complications during pregnancy, conditions of birth, care and morbidities in the NICU. BPD was measured for premature neonates using oxygen therapy for a period equal to or greater than 28 days or 36 weeks of corrected gestational age. After bivariate analyses, binary logistic regression analysis was followed. For the final model, a significance level of 5% (p<0.05) was defined, with registration of the respective Odds Ratio and 95% confidence intervals. Results: data from 293 preterm infants, predominantly male (55.6%) with gestational age from 32 to 36 weeks, were evaluated. BPD was recorded for 63 children (21.5%). The variables that remained statistically associated with BPD were: birth weight, gestational age and late sepsis. Conclusions: there was a high incidence of BPD. Associated factors highlight the need for improving preand postnatal care.